The SUM of TWO NUMBERS is 4 and THEIR DIFFERENCE is ZER0.

x +y = 4

x-y = 0

Adds the equations together... 2x = 4 ---> x = 2 then y=2

2+2=4 and 2-2=0

Lena M.

asked • 08/13/20**Whats the answer to this?**

More

The SUM of TWO NUMBERS is 4 and THEIR DIFFERENCE is ZER0.

x +y = 4

x-y = 0

Adds the equations together... 2x = 4 ---> x = 2 then y=2

2+2=4 and 2-2=0

Justice R. answered • 08/14/20

Tutor

5
(11)
Child Development Student & Writer Teaching to Multiple Intelligences

This is listed under elementary math. Are you working with variables yet? ("Variables" are letters, like x and y, used to replace numbers in pre-algebra and algebra.) If you are, check out the answers other tutors gave.

If not, here's how to solve the problems without variables!

**Step 1. **Think of all the combinations you can that add up to four. To simplify it, let's start by using *just* positive numbers and zero.

0+4

1+3

2+2

3+1

4+0

And.... stop! That's it. Those are all the combinations of non-negative numbers that add up to four.

**Step 2. **Let's take out any number combinations that are repeats. For example, 0+4 is the same as 4+0, and 1+3 is the same as 3+1.

0+4

1+3

2+2

~~3+1~~

~~4+0~~

That leaves:

0+4

1+3

2+2

**Step 3. **Let's do subtraction with each of these pairs, and see which gives us zero.

0 - 4 = -4

4 - 0 = 4

So it's not 0, 4!

1 - 3 = -2

3 - 1 = 2

So it's not 1, 3!

2 - 2 = 0

So that's it!

**Solution: **2+2=4, and 2-2=0. The answer is 2 and 2.

Mahesh T. answered • 08/13/20

Tutor

New to Wyzant
TEACHING IS MY PASSION

Steps using Substitution – To solve a pair of equations using Substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.

X + Y = 4 , X – Y = 0

X + Y = 4

X = - Y + 4

- Y + 4 – Y = 0

- 2Y + 4 = 0

- 2Y = - 4

Y = 2

X = -2 + 4

X = 2 , Y = 2

Steps using Elimination – In order to solve by Elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.

X + y = 4 , x – y = 0

X – X + Y + Y = 4

Y + Y = 4

2Y = 4

Y = 2

X – 2 = 0

X = 2

X = 2 , Y = 2

Let x and y be the two numbers

x + y = 4

x - y = 0

Add the two equations together

2x = 4

solve for x

x = 2

Since x + y = 4 and x = 2, then y = 2

check: 2 + 2 = 4

2 - 2 = 0

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.

Justice R.

If your child is not yet using negative numbers, here's a more age-appropriate way to perform Step 3: Let's do subtraction with each of these pairs, and see which gives us zero. 4 - 0 = 4. So it's not 0, 4! ..... 3 - 1 = 2. So it's not 1, 3! ..... 2 - 2 = 0. So that's it!08/14/20